2021
DOI: 10.1002/aelm.202100255
|View full text |Cite
|
Sign up to set email alerts
|

High Electrical Anisotropic Multilayered Self‐Assembled Organic Films Based on Graphene Oxide and PEDOT:PSS

Abstract: Multilayered self‐assembled structures having different constituents are very appealing for preparing novel materials with unusual electrical phenomena not observed on the individual sheets. Here, the fabrication and characterization of aligned multilayered architectures comprised of reduced graphene oxide (rGO) and poly(3,4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), embedded into polymer electrolytes, are reported. The in‐plane conductivity is five orders of magnitude higher than the cross‐pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
(107 reference statements)
0
4
0
Order By: Relevance
“…The anisotropic film operates simultaneously as a dielectric layer and as an ambipolar transistor channel, paving the way for fabricating dual-channel inverters. [45] In our work, the introduction of PEDOT:PSS can greatly improve the conductivity of the hybrid electrodes because of the higher conductivity of PEDOT:PSS (typically over 1000 S cm −1 ) than that of rGO (typically at 3.33-71 S cm −1 ). [17,46,47] The low conductivity of rGO originates from the loss of carbon during reduction, residual oxygenated sites, and the physical grain boundaries between the original GO sheets.…”
Section: Resultsmentioning
confidence: 80%
“…The anisotropic film operates simultaneously as a dielectric layer and as an ambipolar transistor channel, paving the way for fabricating dual-channel inverters. [45] In our work, the introduction of PEDOT:PSS can greatly improve the conductivity of the hybrid electrodes because of the higher conductivity of PEDOT:PSS (typically over 1000 S cm −1 ) than that of rGO (typically at 3.33-71 S cm −1 ). [17,46,47] The low conductivity of rGO originates from the loss of carbon during reduction, residual oxygenated sites, and the physical grain boundaries between the original GO sheets.…”
Section: Resultsmentioning
confidence: 80%
“…Typical output characteristics of SiOECTs with functionalized gate electrode operating in depletion mode was shown in Fig. S7 [ 28 , 29 ]. The drain-source current (I DS ) decreased with increasing bias gate voltage (V G ) [ 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…LbL assembly presents a promising approach for creating composite graphitic materials with electrical anisotropy, achieved through simple and affordable experimental protocols. A recent study by Gomes et al [81] reported the fabrication of a self-assembled multilayer composite based on graphene, exhibiting remarkably high electrical anisotropy, with in-plane conductivity measuring five orders of magnitude higher than cross-plane conductivity. This unique property of LbL-assembled materials opens up possibilities for utilizing them as semi-insulators for cross-plane conduction and semiconductors for in-plane conduction.…”
Section: Fets Based On Multilayered Graphene Oxide and Pedot:pssmentioning
confidence: 99%